1999
DOI: 10.4049/jimmunol.162.5.2842
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Dormancy. VII. A Regulatory Role for CD8+ T Cells and IFN-γ in Establishing and Maintaining the Tumor-Dormant State

Abstract: Dormant tumor cells resistant to ablative cancer therapy represent a significant clinical obstacle due to later relapse. Experimentally, the murine B cell lymphoma (BCL1) is used as a model of tumor dormancy in mice vaccinated with the BCL1 Ig. Here, we used this model to explore the cellular mechanisms underlying dormancy. Our previous studies have demonstrated that T cell-mediated immunity is an important component in the regulation of tumor dormancy because Id-immune T cells adoptively transferred into pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Similarly studies on a B-cell lymphoma that establishes dormancy through a vaccination protocol revealed important components on how dormancy could be induced and maintained by CD8+ T cells and IFNγ signaling 6 . Additionally, immune evasion was shown to allow the persistence of dormant leukemic cells in mouse acute myeloid leukemia (AML) through the upregulation of B7-H1 (PD-L1)…”
Section: Autophagy and Metabolismmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly studies on a B-cell lymphoma that establishes dormancy through a vaccination protocol revealed important components on how dormancy could be induced and maintained by CD8+ T cells and IFNγ signaling 6 . Additionally, immune evasion was shown to allow the persistence of dormant leukemic cells in mouse acute myeloid leukemia (AML) through the upregulation of B7-H1 (PD-L1)…”
Section: Autophagy and Metabolismmentioning
confidence: 98%
“…The cancer dormancy field has worked based on three definitions that are not necessarily mutually exclusive and may be complementary. These have led to the working hypothesis that asymptomatic minimal residual disease (MRD) can be defined and explained by three potential scenarios: 1) angiogenic dormancy, an impaired angiogenic response maintaining tumor mass constant in size by balancing proliferation and cell death [1][2][3] ; 2) immune-mediated dormancy, in which proliferative tumor cell populations are constantly trimmed by cytotoxic immune cell responses that also maintain an equilibrium between cell death and proliferation [4][5][6][7][8][9][10][11][12][13] ; and 3) cellular dormancy, in which solitary DTCs or small cell clusters enter a prolonged growth arrest with no increase in cell death 19,[24][25][26][27] .…”
Section: Discussing Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…IFNγ is mainly produced by T cells, natural killer (NK) cells and NK T cells, 21 if CD8+ T cells inhibit tumor growth by producing IFNγ, and at the same time, we can also inhibit or downregulate TBX2, IFNγ‐induced downregulation of IRF1 can be promoted, thereby downregulate PD‐L1, resulting in promoting T cell killing. Previous studies have shown that the dormant state of tumors can determine whether IFNγ can suppress dormant cells or edit dormant tumor cells, leading to tumor recurrence 22 . In particular, Ki67‐low indolent cancer cells are vulnerable to immunomodulation that can evade immunotherapy, whereas Ki67‐quiescent dormant cells are not immune‐modulated and thus remain dormant by IFNγ‐producing T cells 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Immune-mediated tumor mass dormancy can also control the development and growth of dormant tumor lesions. Thus, the survival and continued growth of primary and secondary tumor foci requires the evasion of the host immune response [ 123 , 124 ]. This mechanism of dormancy is evoked when the rate at which immune-mediated cancer cell cytotoxicity equals cancer cell proliferation, resulting in a malignant mass with a stable size [ 125 ].…”
Section: Dormancy Of Micro-metastatic Focimentioning
confidence: 99%